GE_GERICHTE P/26530/2022 vom 22. Juli 2024 - GE Cour de justice (2024)
ORDONNANCE PÉNALE;CITATION À COMPARAÎTRE;DÉFAUT(CONTUMACE);CLASSEMENT DE LA PROCÉDURE;PRINCIPE DE LA BONNE FOI | CPP.356.al4; CPP.329.al1.letb; CPP.329.al4; Cst